A walk on the wild side: An investigation into the quantity and quality of "predatory" publications in Italian academia - Manuel F. Bagues; Mauro Sylos Labini; Natalia Zinovyeva (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2017)
In recent years the academic world has experienced a mushrooming of journals that falsely pretend to provide peer review. We study the quantity and quality of publications in dubious journals using information from the CVs of 46,000 researchers seeking promotion in Italian academia. We find that about 5% of these researchers have published in journals included in the blacklist of "potential, possible, or probable predatory journals" elaborated by the scholarly librarian Jeffrey Beall. To better understand the quality of these publications and the motivations of authors, we collected bibliometric information and we conducted a survey among one thousand researchers (response rate=54%). According to respondents, at least a third of these journals either did not offer regular peer review or engaged in some type of irregular editorial practice. The proportion of journals with reported malpractices is similar among journals from Beall's list that are indexed in Scopus. On the other hand, we also find evidence suggesting that some journals identified by Beall may be legitimate. Overall, our results indicate that the use of white and black lists in research evaluations needs to be complemented with expert evaluations.
Keywords: I23; J45; 330; predatory journals; Italian academia; scientific misconduct